Flexible bio-composites with continuous natural fibre and bamboo charcoal: enhanced flame retardancy, mechanical resilience, energy-absorbing & printability performance - Kaveh Rahmani; Callum Branfoot; Sarah Karmel; Kevin Lindsey; Mahdi Bodaghi (Virtual and Physical Prototyping)
This study presents a novel sustainable flexible bio-composite reinforced with bamboo charcoal (BC) and continuous flax fibres (CFF), designed to achieve exceptional thermo-mechanical features. Unlike conventional 3D-printed composites that rely on synthetic reinforcements, this research pioneers the synergistic integration of BC and CFF within a bio-based thermoplastic polyurethane (TPU) matrix using dual-feed 3D printing. BC/CFF incorporation enhances interfacial adhesion, as evidenced by scanning electron microscopy, leading to superior load transfer efficiency. Dynamic mechanical analysis confirms a substantial increase in storage modulus, improving structural stiffness, while melt flow index assessments demonstrate retained extrudability/printability. The addition of 3 wt.% BC and CFF achieves a 1571% increase in tensile strength relative to pure TPU. Furthermore, flame retardancy is significantly improved, with a 52% reduction in burning rate, achieving a UL-94 V-1 rating and a limiting oxygen index of 29.5% vol. Cyclic tensile tests reveal hyper-visco-pseudo-elastic behaviour, stress softening, and high energy-dissipation capacity, confirming suitability for dynamic applications. Meta-bio-composites with quasi-zero stiffness, force regulation, and superior energy absorption/dissipation exhibit a 933% improvement in specific energy absorption, making them ideal for protective applications. These findings establish bio-composites and their meta-structures as high-performance, sustainable alternatives to synthetic counterparts, unlocking new possibilities for automotive/logistics/furniture, and safety-critical applications.